Java EE 7 First Look. - Armel Fabrice, NDJOBO (Packt Publishing, 2013)
An easy-to-follow guide to reveal the new features of Java EE 7 and how to efficiently utilize them. Given the main objectives pursued, this book targets three groups of people with a knowledge of the Java language. They are:Beginners in the Java EE platform who would like to have an idea about the main specifications of Java EE 7. Developers who have experimented with previous versions of Java EE and who would like to explore the new features of Java EE 7. Building architects who want to learn how to put together the various Java EE 7 specifications for building robust and secure enterprise appl.